Skogsmarksgödsling : en ekonomisk analys av olika gödslingsstrategier för ett skogsinnehav i norra Sverige - Bergsten, Marcus (SLU/Dept. of Forest Resource Management, 2005)
The purpose of this study is to analyze the economic effects of different fertilization programs both on stand- and forest-level. The study is applied on an objective sample of inventory data for a forest area in Kalix in northern Sweden. The forest area belongs to the forest company Sveaskog. The study includes different economic models and will be used as a support when the company decides how to invest and how much to invest in fertilization. The study investigates the economy of five different fertilization policies. For each program the rate of interest invested in fertilization and the cost for the extra produced volume has been calculated. One part of the study includes fertilization at a forest-level context and the results show how the different programs affect annual cut volume and NPV (net present value). The programs included in the study are based on the theory that fertilization should be carried out ten years before thinning or clear cutting because then the invested capital is not bound longer then necessary and the fertilization effect has been utilized. Among the programs included in the study, fertilization ten years before clear cutting gives the highest interest on invested capital. Fertilization ten years before thinning produces extra volumes to a lower cost than fertilization ten years before clear cutting. Fertilization before all thinning and clear cut gives the highest NPV and highest annual cut volume. A program with fertilization before all harvest activities makes it possible to increase the annual cut volume with 7-12 % on forest-level depending on demands on interest and tolerance to fluctuation in harvested volume between periods. Detta examensarbete analyserar de ekonomiska effekterna av olika gödselprogram i enskilda bestånd samt på innehavsnivå på Sveaskogs innehav i Kalix beräkningsområde. Arbetet omfattar olika ekonomiska modeller och ska fungera som beslutsstöd vid budgetarbete inför år 2006 där Sveaskog står inför beslut om storskalig satsning på gödsling. Studien ...